2022
DOI: 10.21203/rs.3.rs-2228576/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly host-linked viromes in the built environment possess habitat-dependent diversity and functions for potential virus-host coevolution

Abstract: Viruses in built environments (BEs) raise public health concerns, yet they are generally less studied than bacteria. To better understand viral dynamics in BEs, this study assessed viromes from 11 habitats across four types of BEs with low to high occupancy. The diversity, composition, metabolic functions, and lifestyles of the viromes were found to be habitat dependent. Caudovirales species were ubiquitous on surface habitats in the BEs, and some of them were distinct from those present in other environments.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Bacteriophages can insert AMGs into their hosts that help them adapt to their environment 22,48 . In the present study, we found evidence that an AMG encoding an arylalcohol dehydrogenase 49 was inserted into a bacterium in cutotype 2 under high-PAH exposure conditions, suggesting that this enzyme may help the bacterium to biodegrade xenobiotics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bacteriophages can insert AMGs into their hosts that help them adapt to their environment 22,48 . In the present study, we found evidence that an AMG encoding an arylalcohol dehydrogenase 49 was inserted into a bacterium in cutotype 2 under high-PAH exposure conditions, suggesting that this enzyme may help the bacterium to biodegrade xenobiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Three complementary in silico methods were adopted to improve the accuracy of host prediction, namely methods that find exact or close matches of CRISPR spacers and integrated viral fragments in host genomes and a method that finds consistent k-mer signatures, as described previously 48 . Briefly, CRISPR spacers in the rMAGs were identified using CRT (v.1.2) 91 and PILER-CR (v.1.0.6) 92 .…”
Section: Determination Of Virus-host Linksmentioning
confidence: 99%
See 2 more Smart Citations